The performance of de novo commercial banks: A profit efficiency approach - DeYoung, Robert; Hasan, Iftekhar (Journal of Banking & Finance, 1998)
We examine the profit efficiency of US banks chartered between 1980 and 1994. Our results suggest that profit efficiency improves rapidly at the typical de novo bank during its first three years of operation, but on average takes about nine years to reach established bank levels. Excess branch capacity, reliance on large deposits, and affiliation with a multibank holding company are associated with low profit efficiency at de novo banks. De novo national banks are initially less profit efficient than are state-chartered de novos, perhaps reflecting differences in the chartering philosophy of federal and state bank regulators.